Hymenasplenium pubirhizoma comb. nov. (Aspleniaceae) from China - Xu, Ke-Wang; Lu, Jin-Mei; Zhang, Xin; Zhang, Li-Bing (Phytotaxa, 2018)
An earlier known species originally assigned to Asplenium from China, A. pubirhizoma Ching & Z.Y.Liu, is transferred to Hymenasplenium to form H. pubirhizoma (Ching & Z.Y.Liu) K.W.Xu & Li Bing Zhang, comb. nov.